Implementation of inclusive school program management - Trinarti, Trinarti; Safitri, Emilia (Journal of Advanced Islamic Educational Management, 2024)
This thesis discusses the Implementation of the Inclusive School Program Management at SMP Negeri 14 Bandar Lampung. The problem is discussed through a field study. This type of research is qualitative research. The data was obtained by using, observation, interviews and documentation. All data obtained were then analyzed using qualitative data analysis. The results of the study found that: 1) Inclusive school planning is carried out by planning students, curriculum and teaching staff. infrastructure, and financing. 2) Organizing inclusive schools at SMP Negeri 14 Bandar Lampung by dividing tasks, there is someone appointed as the person in charge of implementing inclusive education, assisted by class teachers, subject teachers and accompanying teachers; 3) The implementation of inclusive schools uses the modified K-13 curriculum and the learning model uses Two Teachers, which is learning carried out by two teachers; 4) Monitoring of the inclusive school at SMP Negeri 14 Bandar Lampung is carried out every three months. This monitoring is also carried out by sharing the evaluation results of students with special needs which will be submitted to the students' guardians. In addition, every month a monthly meeting is held as a way of direction and control.